Analisis Angkutan Sedimen Total pada Sungai Dawas Kabupaten Musi Banyuasin - Hendar Pangestu; Helmi Haki (Jurnal Teknik Sipil dan Lingkungan, 2013)
In the cycle’s,  river will through the process due to the silting of the river bed sediment movement caused by the river flow and erosion. Sedimentation process is part of the process of soil erosion. This activity takes place either due to water or wind. Dawas river have an important role for the community, because the river flows dawas used as a means of public transport locals and surrounding, but it is also used to support the pace of economic growth for the surrounding area. Occurring due to silting in the river dawas, causing disruption of activity surrounding communities, therefore conducted research on the total sediment transport analysis using several methods in order to determine how much capacity the total sediment transport occurring dawas river, The results of this study can be seen the average sediment discharge, using the Yang’s Method get 0.00007532 ton/s,, using the Bagnold’s Methode obtained  0.00007418 ton/s and using the Shen and Hung’s methode get 0.00007 ton/s. Keywords: Cycle, Rivers, Sedimentation, Erosion, Yang's method, Bagnold’s Method and Shen and Hung's Method